INVENTARISASI KELAS PISCES DI PASAR TRADISIONAL SUNGGUMINASA KABUPATEN GOWA SEBAGAI SUMBER BELAJAR TAKSONOMI VERTEBRATA DALAM BENTUK MODUL - Hafsah, Hafsah (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2024)
This research was conducted at the Sungguminasa traditional market, Gowa Regency because of its strategic location and the product prices offered are more economical. This research aims to inventory the types of fish in the Sungguminasa Gowa Traditional Market to be used as teaching material for students studying the Vertebrate Taxonomy course. Data collection techniques to obtain data are carried out through observation, interviews and documentation with sources. Data analysis was carried out descriptively. The results of the research showed that the types of fish found at the research location were layang fish, cakalang fish, sibula